Development and results of a patient-reported treatment experience questionnaire on a 1.5 T MR-Linac - Helen Barnes; Sophie Alexander; Lorna Bower; Jakob Ehlers; Cihan Gani; Trina Herbert; Rebekah Lawes; Pia Krause Møller; Toby Morgan; Marlies E. Nowee; Gillian Smith; Baukelien van Triest; et al. (Clinical and Translational Radiation Oncology, 2021)
Introduction: With the implementation of new radiotherapy technology, it is imperative that patient experience is investigated alongside efficacy and outcomes. This paper presents the development of a specifically designed validated questionnaire and a first report of international multi-institutional preliminary patient experience of MRI-guided adaptive radiotherapy (MRgART) on the 1.5 T MR-Linac (MRL). Methods: A patient experience questionnaire was developed and validated before being distributed to the Elekta MRL Consortium, to gather first patient-reported experience from participating centres worldwide. The final version of the questionnaire contains 18 questions covering a range of themes and was scored on a Likert scale of 0–3. Responses were post-processed so that a score of 0 represents a negative response and 3 represents the most favourable response. These results were analysed for patient-reported experience of treatment on the MRL. Results were also analysed for internal consistency of the questionnaire using Chronbach’s Alpha and the questionnaire contents were validated for relevance using content validity indexes (CVI). Results: 170 responses were received from five centres, representing patients with a wide range of tumour treatment sites from four different countries. MRgART was well tolerated with an 84% favourable response across all questions and respondents. When analysed by theme, all reported the highest percentage of results in the favourable categories (2 and 3). Internal consistency in the questionnaire was high (Cronbach’s α = 0.8) and the item-level CVI for each question was 0.78 or above and the Scale-level CVI was 0.93, representing relevant content. Conclusion: The developed questionnaire has been validated as relevant and appropriate for use in reporting experience of patients undergoing treatment on the MRL. The overall patient-reported experience and satisfaction from multiple centres within the Elekta MRL Consortium was consistently high. These results can reinforce user confidence in continuing to expand and develop MRL use in adaptive radiotherapy.